The Edinburgh companion to modernism and technology - Goody, Alex; Whittington, Ian (Edinburgh University Press, 2022)
The first comprehensive reference book to define and delineate the intersections of modernism and technology.
Keywords: Literature, Modern -- 20th century -- History and criticism.; Modernism (Literature); Literature and technology.; Littérature -- 20e siècle -- Histoire et critique.; Modernisme (Littérature); Littérature et technologie.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Literature and technology; Literature, Modern; 1900-1999; Criticism, interpretation, etc.